2017
DOI: 10.1111/crj.12639
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermal imaging and Doppler vessel pressurization ultrasonography to detect lower extremity deep vein thrombosis: Diagnostic accuracy study

Abstract: IRTI could be used to supplement CPUS detection for detecting DVTs and adjunctive diagnostic screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Furthermore, the human skin with an emissivity value of 0.98, is a near‐ideal radiator in the infrared domain 16 . In this regard, there is emerging literature on the utility of IRT for detection of peripheral arterial disease (PAD), deep vein thrombosis (DVT), diabetic vasculopathy and neuropathy, posttraumatic acute compartment syndrome, and other vascular diseases 20,23–33 . Multiple studies have also demonstrated a good correlation between IRT and other established diagnostic tools, such as ankle‐brachial index for diagnosis of PAD and Doppler ultrasound for DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the human skin with an emissivity value of 0.98, is a near‐ideal radiator in the infrared domain 16 . In this regard, there is emerging literature on the utility of IRT for detection of peripheral arterial disease (PAD), deep vein thrombosis (DVT), diabetic vasculopathy and neuropathy, posttraumatic acute compartment syndrome, and other vascular diseases 20,23–33 . Multiple studies have also demonstrated a good correlation between IRT and other established diagnostic tools, such as ankle‐brachial index for diagnosis of PAD and Doppler ultrasound for DVT.…”
Section: Discussionmentioning
confidence: 99%
“…In order to further verify the clinical value of infrared thermal imaging, this method was compared with Doppler compression ultrasonography in terms of deep vein thrombosis [31]. The results revealed the sensitivity at the level of 88.3%, the specificity of 65.0%, and a diagnostic accordance rate of 75.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Through non-invasive imaging of venous vessels and their surrounding tissues, dynamic blood circulation of venous vascular tissues can be observed to determine the location and severity of DVT. According to relevant data, the accuracy of colour Doppler ultrasound in the diagnosis of DVT is more than 75% [31]. The incidence of postoperative DVT was 62.96% in the control group and 14.81% in the observation group.…”
Section: Popliteal Vein Embolizationmentioning
confidence: 99%